Review of the genus Dolichosciara Tuomikoski (Diptera, Sciaridae) from China - Wu, Hong; Shi, Kai; Huang, Junhao; Zhang, Sujiong (Zootaxa, 2013)
The genus Dolichosciara from China is reviewed and 17 species are recognized. Among them, eight new species, D. sparsula sp. nov., D. gracilenta sp. nov., D. oxyacantha sp. nov., D. scrobiculata sp. nov., D. tumidula sp. nov., D. rectospinosa sp. nov., D. multisetosa sp. nov. and D. qingliangfengana sp. nov. are described and seven species, D. ninae (Antonova, 1977), D. megumiae (Sasakawa, 1994), D. orcina (Tuomikoski, 1960), D. semiferruginea (Menzel, 1995), D. hippai Komarova & Vilkamaa, 2006, D. subornata (Mohrig & Menzel, 1994) and D. ornata (Winnertz, 1867) are reported for the first time from China. In addition, geographical distribution of 17 Chinese species are provided, as well as a key to all these Chinese species. This study raises the number of the species of Chinese Dolichosciara from 2 to 17.